(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2019)
The water of different rivers passing in the Sundarban Mangrove Forests (SMF) of Bangladesh was analyzed to know the spatio-temporal variations in the water quality and phytoplankton diversity of the river. The pH of the waters of all the rivers examined showed a narrow range of variation (6.60-7.8 in 2015 and 6.3 to 7.5 in 2016) indicating the buffering capacity of different rivers. The values of pH showed a slightly decreasing tendency indicating the acidification of river waters which might be due to increase of global CO2 concentration in the atmosphere. The temperature of water, conductivity, salinity, DO (ppm), DO (% sat), K, Na, was found to vary from 27.6 to 30.8° C, 8.00 to 32.30 mS/cm, 5.50 to 23.00 ‰, 3.5 to 6.35 ppm, 46.60 to 82.00 %, 125.00 to 630.00 mg/l, 600 to 4300 ppm, respectively in April 2015; and ranged from 28.8 to 31.0° C, 9.48 to 31.60 mS/cm 5.00 to 24.00 ‰, 0.11 to 5.33 ppm, 1.2 to 95.2 % saturation, 110 to 670 ppm, 4683.5 to 13465.10 ppm, respectively in March 2016. The values of Ca, Mg and Fe were 210 to 500 ppm, 320.0 mg/l to 892.0 mg/l and 0.25 to 0.050 mg/l, respectively in 2015. The amount of DO was very low during 2016 especially in the locations 1, 2, 3 which might be due to cloudy condition during sampling time. Principal component analyses (PCA) of different variables of the year 2015 showed that PC-1 had positive loading of water temperature, air temperature, humidity, pH, conductivity, Salinity, Na, K, Fe, Mg, Zn whereas PC-1 of different variables during 2016 showed positive loading of only water temperature and pH. Maximum number of phytoplankton taxa was recorded from Sela river (Tambulbunia) where 34 taxa (with the unknown ones) were recorded followed by Passur river (near Mongla Ferry Ghat). Coscinodiscus is found to be the dominant genus. Maximum Shannon-Weaver index of diversity was found in Homra Khal (value was 6.825) and minimum was found in Sela river (where the oil tanker sank and value was 0.0). Only one species of phytoplankton was found in this place. Maximum species richness (d) was observed in Passur river at Mongla ferry ghat with a value of 14.81 whereas, maximum evenness (e) was found in location 16 (Homra khal with a value of 5.437). J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 61-76